Tren Publikasi Ilmiah dalam Kajian Digitalisasi Pelayanan Publik : Analisis Bibliometric Data Scopus - Jiwa Riwayanti; Bambang Suprianto (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study examines trends in scientific publications on digitalization from 2014 to 2024 published in Scopus-indexed journals worldwide. Data were collected from the Scopus database on October 6, 2024, at 21:56 WIB using the keywords